(C+5)+(c-1)=90

Simple and best practice solution for (C+5)+(c-1)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (C+5)+(c-1)=90 equation:


Simplifying
(C + 5) + (c + -1) = 90

Reorder the terms:
(5 + C) + (c + -1) = 90

Remove parenthesis around (5 + C)
5 + C + (c + -1) = 90

Reorder the terms:
5 + C + (-1 + c) = 90

Remove parenthesis around (-1 + c)
5 + C + -1 + c = 90

Reorder the terms:
5 + -1 + C + c = 90

Combine like terms: 5 + -1 = 4
4 + C + c = 90

Solving
4 + C + c = 90

Solving for variable 'C'.

Move all terms containing C to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + C + -4 + c = 90 + -4

Reorder the terms:
4 + -4 + C + c = 90 + -4

Combine like terms: 4 + -4 = 0
0 + C + c = 90 + -4
C + c = 90 + -4

Combine like terms: 90 + -4 = 86
C + c = 86

Add '-1c' to each side of the equation.
C + c + -1c = 86 + -1c

Combine like terms: c + -1c = 0
C + 0 = 86 + -1c
C = 86 + -1c

Simplifying
C = 86 + -1c

See similar equations:

| 4y+6(y+8)= | | 3(x+1)+4x=24 | | 18.1--0.7=c | | 75c^2+90cd+27d^2= | | 18.1--0.7= | | 16x^2-38x-5= | | 9=-7y+8 | | y=(3)(-1)-2 | | 79=8x-11 | | 5m-8.5=3.7m+4.37 | | 16x^2-38c-5= | | 2m^2-29m+60=0 | | y=(3)(1)-2 | | 1.5x+.7=10.7+.5x | | 7x+6=8-(7x-6) | | -2(5k-1)=22 | | 5n+7+7=3n-2+2(2n+1) | | y=(3)(0)-2 | | 5y-81x=0 | | 50x+6=6+50x | | x-5+14=24 | | 2a^2-25a+50=0 | | 4+2.3t=1.7 | | (3x-5)+(8x-13)=180 | | 5u+18=58 | | (3d+4)+(2d-9)=180 | | 4b-6+2r=-48 | | 3x+12=5x+42 | | a+2s=3(s-2)+1 | | x^2+17x-193=0 | | t=x^2+3x | | 2a^2+23a+45=0 |

Equations solver categories